2021
DOI: 10.3390/cells10102594
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Clearance of Immune Cells in Cardiovascular Disease

Abstract: Recent advances in our understanding of the lymphatic system, its function, development, and role in pathophysiology have changed our views on its importance. Historically thought to be solely involved in the transport of tissue fluid, lipids, and immune cells, the lymphatic system displays great heterogeneity and plasticity and is actively involved in immune cell regulation. Interference in any of these processes can be deleterious, both at the developmental and adult level. Preclinical studies into the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…It is known that the passage of immune cells from tissue interstitium toward afferent lymphatic vessels depends on chemotaxis ( 18 ). Previous investigations showed that lymphatic endothelium expressed and secreted various chemokines, including CCL2, CCL12, CCL5, CCL20, CXCL2, and CX3CL1 (fractalkine), which direct selective egress from tissues of leukocytes ( 26 ). We next asked whether LEC-S1pr1 regulated the expression of chemokines, which directs leukocytes toward LECs and enhanced their egress from injured hearts.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the passage of immune cells from tissue interstitium toward afferent lymphatic vessels depends on chemotaxis ( 18 ). Previous investigations showed that lymphatic endothelium expressed and secreted various chemokines, including CCL2, CCL12, CCL5, CCL20, CXCL2, and CX3CL1 (fractalkine), which direct selective egress from tissues of leukocytes ( 26 ). We next asked whether LEC-S1pr1 regulated the expression of chemokines, which directs leukocytes toward LECs and enhanced their egress from injured hearts.…”
Section: Discussionmentioning
confidence: 99%
“…That said, tumors might also influence the composition of residing progenitors as suggested by dominance of the CD11b + /Lyve-1 + population as compared with minor CD3e + and Ter-119 + subsets. The preference for expansion of lymphatics can be explained by their unique and essential role in removing stimulatory immune cells [86] and debris [87] that otherwise sustain chronic inflammation [88] and block tissue repair [89]. Therefore, increased lymphatics address the most pressing tumor need for regeneration that is less likely to be supported by local production of T-cells or erythrocytes plentifully supplied by blood vessels.…”
Section: Plos Onementioning
confidence: 99%
“…Lymphatic vasculature also plays an important role during cardiac regeneration by enhancing immune cell trafficking and in doing so, reducing inflammation ( 87 ). During the process of remodeling which occurs in the failing heart, angiotensin II (AngII) is expressed and associated with dysfunctions such as the misexpression of lymphatic vessel endothelial hyaluronan receptor 1 (LYVE1) and VEGFC.…”
Section: Mechanisms Underlying Heart Regenerationmentioning
confidence: 99%